2020
DOI: 10.1101/2020.09.03.282251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inferring number of populations and changes in connectivity under the n-island model

Abstract: Inferring the demographic history of species is one of the greatest challenges in populations genetics. This history is often represented as a history of size changes, thus ignoring population structure. Alternatively, structure is defined a priori as a population tree and not inferred. Here we propose a framework based on the IICR (Inverse Instantaneous Coalescence Rate), which can be estimated using the PSMC method of Li and Durbin (2011) for a single diploid individual. For an isolated population, the IICR … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The models described in the present study propose another direction for the development of demographic inference methods by accounting for linked selection through variable classes of N e along the genome, and using the IICR as summary statistic. An IICR-based inference framework was recently proposed for the estimation of non stationary n-island models and provided very encouraging results (Arredondo et al, 2021). Given the strong impact of linked selection on the IICR under panmixia, as described in the present study, we believe that a similar approach could allow to jointly infer parameters related to demographic history and to the N e distribution.…”
Section: Perspectivesmentioning
confidence: 62%
See 4 more Smart Citations
“…The models described in the present study propose another direction for the development of demographic inference methods by accounting for linked selection through variable classes of N e along the genome, and using the IICR as summary statistic. An IICR-based inference framework was recently proposed for the estimation of non stationary n-island models and provided very encouraging results (Arredondo et al, 2021). Given the strong impact of linked selection on the IICR under panmixia, as described in the present study, we believe that a similar approach could allow to jointly infer parameters related to demographic history and to the N e distribution.…”
Section: Perspectivesmentioning
confidence: 62%
“…Considering a symmetrical n-island model, we observed for instance that even when a large proportion of the genome is influenced by selection reducing N e the effect on the IICR could be difficult to see for models with reduced migration rates between islands (Figure 4). Focusing on humans we also considered a simple but reasonable demographic scenario of variable population structure Arredondo et al (2021) together with a realistic genomic N e distribution for this species Gossmann et al (2011). We found that the largest and most visible effect of linked selection on the IICR was an ancient population size increase (backward in time) related to the presence of balancing selection (Figure 5, bottom).…”
Section: Effects Of Linked Selection On the Iicrmentioning
confidence: 99%
See 3 more Smart Citations